STUDENTS’ PERCEPTIONS IN THE IMPLIMENTATION OF ROLE PLAY IN INCREASING SPEAKING SKILL AT SMP NEGERI 4 TONDANO - Feroza Filipi Rotinsulu; Paula Hampp; Jennie Posumah (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
Speaking is one of the important skills in learning language and an indicator to determine people’s understanding especially student, in this case learning English. However, speaking was also a difficult task for student to be mastered due to the lack of confidence and creative method. The purpose of this study was to find out how students’ perception in the implementation of role play activity in speaking English to a junior high school student. This study was conducted at SMP Negeri 4 Tondano using direct questionnaire. In this study, twenty-four of the students from grade VIII were asked to fill and respond to  fifteen questions related to role play activity. Based on the result of the study, it showed that student’s perception toward role play activity was very interesting. All of the participant find role play interesting and help them to improve speaking English. Meanwhile, 75% of the student choose strongly agree that role play is enjoyable for them and 79% of the student agree that role play is an easy way to communicate in English. Then, just 4% of the student said role play is hard and 58% of them says that they need more time to practice role play. It can be concluded that students’ perception in the implementation of role play activity in increasing speaking skills of student at SMP Negeri 4 Tondano was useful and play significant role in increasing student’s confidence and help them to understand English easier in a fun and efficient way.